Thermal Transport in 2D Semiconductors—Considerations for Device Applications. (25th September 2019) - Zhao, Yunshan; Cai, Yongqing; Zhang, Lifa; Li, Baowen; Zhang, Gang; Thong, John T. L.
Abstract: The discovery of graphene has stimulated the search for and investigations into other 2D materials because of the rich physics and unusual properties exhibited by many of these layered materials. Transition metal dichalcogenides (TMDs), black phosphorus, and SnSe among many others, have emerged to show highly tunable physical and chemical properties that can be exploited in a whole host of promising applications. Alongside the novel electronic and optical properties of such 2D semiconductors, their thermal transport properties have also attracted substantial attention. Here, a comprehensive review of the unique thermal transport properties of various emerging 2D semiconductors is provided, including TMDs, black‐ and blue‐phosphorene among others, and the different mechanisms underlying their thermal conductivity characteristics. The focus is placed on the phonon‐related phenomena and issues encountered in various applications based on 2D semiconductor materials and their heterostructures, including thermoelectric power generation and electron–phonon coupling effect in photoelectric and thermal transistor devices. A thorough understanding of phonon transport physics in 2D semiconductor materials to inform thermal management of next‐generation nanoelectronic devices is comprehensively presented along with strategies for controlling heat energy transport and conversion. Abstract : A comprehensive review of thermal transport of various emerging 2D semiconductors is provided here. The phonon‐related phenomenon is discussed alongside issues encountered in various applications based on them. Furthermore, a thorough understanding of phonon transport physics in 2D semiconductors to inform the thermal management of next‐generation nanoelectronic devices is provided, and strategies for controlling heat energy transport and conversion are also considered.